1998
DOI: 10.1103/physrevd.58.096001
|View full text |Cite
|
Sign up to set email alerts
|

Critical region of the finite temperature chiral transition

Abstract: We study a Yukawa theory with spontaneous chiral symmetry breaking and with a large number N of fermions near the finite temperature phase transition. Critical properties in such a system can be described by the mean field theory very close to the transition point. We show that the width of the region where non-trivial critical behavior sets in is suppressed by a certain power of 1/N. Our Monte Carlo simulations confirm these analytical results. We discuss implications for the chiral phase transition in QCD.Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
96
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(122 citation statements)
references
References 18 publications
26
96
0
Order By: Relevance
“…This apparent contradiction was explained in Ref. [7] where, by means of scaling arguments, it was shown that the width of the Ising critical region scales as a power of 1/N f , so that only mean-field behavior can be observed in the limit N f = ∞. An analogous behavior was observed in a generalized O(N) σ model in Ref.…”
Section: Introductionmentioning
confidence: 89%
“…This apparent contradiction was explained in Ref. [7] where, by means of scaling arguments, it was shown that the width of the Ising critical region scales as a power of 1/N f , so that only mean-field behavior can be observed in the limit N f = ∞. An analogous behavior was observed in a generalized O(N) σ model in Ref.…”
Section: Introductionmentioning
confidence: 89%
“…We have studied lattices with temporal extent L t = 16, for which the critical point for the Z 2 symmetric model is estimated to be β T c = 0.790(5) [15], and the high temperature chirally restored phase can thus be studied for β T c < β < β bulk c . A particular virtue of GNM 3 is that, unlike unquenched QCD, it permits a study of hot dynamics with current resources with L t sufficiently large to permit the measurement of thermal masses from correlators in Euclidean time.…”
Section: Nonzero Temperaturementioning
confidence: 99%
“…If the cutoff Λ ≫ T the renormalized selfinteraction coupling λ(T ) in the large-N f limit is close to the IR fixed point of the Yukawa theory and is given by λ(T ) ∼ T Therefore, for d = 3 the Ginzburg criterion for the applicability of the mean field scaling is given by m σ (T ) ≫ T / N f . This scenario was verified numerically in [5]. Additional evidence in favor of the dimensional reduction scenario was produced in studies of the U (1)-symmetric NJL 3 model [6].…”
Section: Universality At Nonzero Temperaturementioning
confidence: 74%